A Novel Sensing Chip for Probing Chlorine Permeation into Simulated Produce Cracks. Issue 13 (10th May 2018) - Guan, Yongguang; Luo, Yaguang; Teng, Zi; Zhou, Bin; Mei, Lei; Bauchan, Gary R.; Wang, Qin
Abstract: Pathogen inactivation efficacy is substantially lower on cracks/crevices than on smooth produce surfaces. In this study, an interlocking design of three‐dimensionally printed chip coated with zein‐ N, N ‐diethyl‐p‐phenylenediamine (DPD) film is developed to study chlorine permeation in simulated cracks. The primary interaction of zein and DPD in film is hydrogen bonding evidenced by the blue shift of the amide II band of zein. The chlorine‐sensing chip exhibits a dose‐dependent magenta color change upon immersion in chlorine solutions. Lab‐scale experiment is performed on chips with full‐depth cracks. At crack widths of 0.2, 0.5, and 1.0 mm, respectively. The static chlorine permeation distances are 11.6, 15.3, and 20.0 mm, when the cracks are perpendicular to the liquid level, compared to 0, 3.3, and 4.3 mm when the cracks are parallel to the liquid level. Complete permeation was detected after dynamic washing for 30 s at chlorine solution Re numbers of 12.5 and 125. In a pilot‐industrial scale washer, chlorine‐permeated distance of 20 mm is detected for full‐depth chlorine‐sensing chips, and 0, 9.4, and 20 mm for half‐depth chips at width of 0.2, 0.5, and 1.0 mm, respectively. Results demonstrated that gravity and boundary pressure facilitates chlorine permeation. This work provides a potential platform for studying the accessibility of sanitizers in narrow gaps under lab‐/industry‐relevant conditions. Abstract : The chlorine‐sensing chip is fabricated by coating zein‐ N, N ‐diethyl‐p‐phenylenediamine (DPD) film on a three‐dimensionally (3D) base chip with interlocking design. This chlorine‐sensing chip exhibits a dose‐dependent magenta color in chlorine solutions with adjustable full‐depth and half‐depth models. This chlorine‐sensing chip can determine the chlorine permeation distances at mimetic crack widths of 0.2‐1.0 mm in both lab‐scale and pilot‐industrial scale washers.